Glucose test provenance recording in UK primary care: was that fasted or random?. Issue 1 (11th February 2016) - McGovern, A. P.; Fieldhouse, H.; Tippu, Z.; Jones, S.; Munro, N.; de Lusignan, S.
Abstract: Aims: To describe the proportion of glucose tests with unrecorded provenance in routine primary care data and identify the impact on clinical practice. Methods: A cross‐sectional analysis was conducted of blood glucose measurements from the Royal College of General Practitioner Research and Surveillance Centre database, which includes primary care records from >100 practices across England and Wales. All blood glucose results recorded during 2013 were identified. Tests were grouped by provenance (fasting, oral glucose tolerance test, random, none specified and other). A clinical audit in a single primary care practice was also performed to identify the impact of failing to record glucose provenance on diabetes diagnosis. Results: A total of 2 137 098 people were included in the cross‐sectional analysis. Of 203 350 recorded glucose measurements the majority (117 893; 58%) did not have any provenance information. The most commonly reported provenance was fasting glucose (75 044; 37%). The distribution of glucose values where provenance was not recorded was most similar to that of fasting samples. The glucose measurements of 256 people with diabetes in the audit practice (size 11 514 people) were analysed. The initial glucose measurement had no provenance information in 164 cases (64.1%). A clinician questioned the provenance of a result in 41 cases (16.0%); of these, 14 (34.1%) required repeating. Lack of provenance led to delays in the diagnosis of diabetes [median (range) 30 (3–614) days]. Conclusions: The recording of glucose provenance in UK primary care could be improved. Failure to record provenance causes unnecessary repeated testing, delayed diagnosis and wasted clinician time. What's new?: It has previously been noted that the recording of provenance data with glucose results is poor, but lack of provenance data has not previously been quantified. We found that 58% of glucose values tested in primary care were recorded without provenance information. A single audit practice showed lack of provenance information lead to delays in diagnosis, unnecessary repeated testing, and wasted clinician time.